1995
DOI: 10.1021/ac00100a011
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Partition Coefficients Chromatographically Measured Using Immobilized Artificial Membrane Surfaces

Abstract: Immobilized artificial membranes (IAMs) are chromatographic surfaces prepared by covalently immobilizing cell membrane phospholipids. IAM surfaces mimic fluid cell membranes. Solute capacity factors (k'IAM) measured on IAM columns correlate very well with solute equilibrium partition coefficients (Km') measured in fluid liposome systems. For 23 structurally unrelated compounds, log-(k'IAM) correlates with log(Km') with a linear correlation coefficient r = 0.907. This indicates that solute partitioning between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(90 citation statements)
references
References 5 publications
2
87
0
1
Order By: Relevance
“…The retention factors were used as descriptors for prediction of the trans-bilayer transport of chemicals. [35][36][37][38] The liposome and IAM binding were correlated for some compounds 39 and not correlated for other compounds. 40 A systematically higher partitioning to IAMs than to liposomes was measured for several other series of compounds.…”
Section: Supported Monolayer Systemsmentioning
confidence: 94%
“…The retention factors were used as descriptors for prediction of the trans-bilayer transport of chemicals. [35][36][37][38] The liposome and IAM binding were correlated for some compounds 39 and not correlated for other compounds. 40 A systematically higher partitioning to IAMs than to liposomes was measured for several other series of compounds.…”
Section: Supported Monolayer Systemsmentioning
confidence: 94%
“…Interesting modifications of this approach are HPLC methods where alkyl chains (e.g., C-18) (Kaliszan, 1990), or carboxyacyl phosphocholine chains (e.g., 11-carboxylundecylphosphocholine) (Ong et al, 1995;Yang et al, 1997) are covalently attached to silica. These systems show a limited anisotropy.…”
Section: Introductionmentioning
confidence: 99%
“…This study stimulated Wainer's group to approach the immobilization process of nicotinic acetylcholine receptors (nAChRs) on lipid monolayers [13]. Interestingly α 3 β 4 nAChRs were also successfully immobilized on the immobilized artificial membrane (IAM) stationary phase, developed by Pidgeon et al [14] and currently available from Regis Technologies, Figure 2. Studies by the Wainer group showed that CMAC prepared with the use of IAM particles were characterized by better reproducibility compared to liposomal columns [13].…”
Section: Cellular Membrane Affinity Chromatography Columns -A Short Hmentioning
confidence: 94%